Barriers to HPV self-sampling and cytology among low-income indigenous women in rural areas of a middle-income setting: a qualitative study - Allen-Leigh, Betania (BMC Cancer, 2017)
BACKGROUND: Data is needed about barriers to self-collection of Human Papillomavirus (HPV) samples and cytology among low-income, disadvantaged women living in rural areas of lower-income countries as these women are at increased risk of cervical cancer mortality. METHODS: Individual interviews (n = 29), focus groups (n = 7, 5–11 participants) and discussion groups (n = 2, 18–25 participants) were organized with women from three indigenous ethnic groups residing in rural areas in Mexico, after they were provided with free, self-sampled HPV tests. These groups are low-income, underserved by healthcare and have historically been on the receiving end of racism and social exclusion. Descriptive, qualitative content analysis was done, including two cycles of coding. RESULTS: Interview and focus/discussion group data indicate women had limited understanding of HPV’s role in cervical cancer etiology. They identified HPV’s existence, that cytology detects cervical cancer, the need for regular testing and that cervical cancer is sexually transmitted. Organizational barriers to clinic-based cytology included irregular supplies of disposable speculums, distance to clinics and lack of clear communication by healthcare personnel. Women considered self-collected HPV-testing easy, less embarrassing and less painful than cytology, an opportunity for self-care and most felt they understood how to take a self-sample after a 20-min explanation. Some women feared hurting themselves when taking the self-sample or that they would take the sample incorrectly, which they worried would make the test useless. Attending HPV-testing in groups facilitated use by allowing women to discuss their doubts and fears before doing self-collection of the sample or to ask other women who were the first to do the self-sampling what the experience had been like (whether it hurt and how easy it was). Lack of indoor bathrooms was a barrier to doing HPV self-sampling at home, when those homes were resource-poor (one-room dwellings). CONCLUSIONS: Low-income, indigenous Mexican women residing in rural, underserved areas identified their need for cervical cancer screening but encountered multiple barriers to cytology-based screening. They found a number of advantages of HPV self-sampled tests. Employing self-collected HPV-testing instead of cytology could resolve some but not all gender-related, organizational or technical quality-of-care issues within cervical cancer detection and control programs. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12885-017-3723-5) contains supplementary material, which is available to authorized users.